Determinants of the use of certified seed potato among smallholder farmers: the case of potato growers in central and eastern Kenya - Okello, J.J.; Zhou, Y.; Kwikiriza, N.; Ogutu, S.O.; Barker, I.; Schulte-Geldermann, Elmar; Atieno, E.; Ahmed, J.T. (MDPI, 2016)
Potato yields in sub-Saharan Africa remain very low compared with those of developed countries. Yet potato is major food staple and source of income to the predominantly smallholder growing households in the tropical highlands of this region. A major cause of the low potato yields is the use of poor quality seed potato. This paper examines the factors determining the decision to use certified seed potato (CSP), as well as the intensity of its use, among potato growers with access to it. We focused on potato growers in the central highlands of Kenya and used regression analysis to test hypotheses relating to potential impediments of CSP use. The study found that the distance to the market (a proxy for transaction costs), household food insecurity, and asset endowment affect the decision to use CSP. However, the effect of the intensity of use of CSP depends on how the intensity variable is defined. Several other control variables also affect the decision and extent of CSP use. The study concludes that transaction costs, asset endowment, and household food insecurity play a major role in the decision by smallholder potato farmers to use CSP and the extent to which they do so. We also discuss the policy implications of the findings.